Pengaruh Inklusi Keuangan, Literasi Keuangan Syariah, Dan Digitalisasi Terhadap Pertumbuhan Aset Bank Umum Syariah - Julaika, Jovita Ika; Febriyanti, Lailatul Ananta (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
This research aims to find out how financial inclusion, Islamic financial literacy, and digitalization affect the asset growth of Islamic Commercial Banks in Indonesia. The reason for this study is the growing importance of giving more people access to financial services, increasing their understanding of Islamic finance, and using digital technology to help Islamic banks grow. This study uses a quantitative approach with secondary data taken from official sources such as the Financial Services Authority (OJK), Bank Indonesia, and the annual reports of Islamic banks from 2020 to 2024. The data is analyzed using multiple linear regression to see the influence of each factor on asset growth. The expected result is that financial inclusion, Islamic financial literacy, and digitalization all have a positive and meaningful impact on the asset growth of Islamic Commercial Banks. This study hopes to support the development of Islamic banking strategies that are more inclusive, educational, and digital-friendly.